A study on the ability of quaternary ammonium groups attached to a polyurethane foam wound dressing to inhibit bacterial attachment and biofilm formation. Issue 1 (13th February 2015) - Tran, Phat L.; Hamood, Abdul N.; de Souza, Anselm; Schultz, Gregory; Liesenfeld, Bernd; Mehta, Dilip; Reid, Ted W.
Abstract Bacterial infection of acute and chronic wounds impedes wound healing significantly. Part of this impediment is the ability of bacterial pathogens to grow in wound dressings. In this study, we examined the effectiveness of a polyurethane (PU) foam wound dressings coated with poly diallyl‐dimethylammonium chloride (pDADMAC‐PU) to inhibit the growth and biofilm development by three main wound pathogens, Staphylococcus aureus, Pseudomonas aeruginosa, and Acinetobacter baumannii, within the wound dressing. pDADMAC‐PU inhibited the growth of all three pathogens. Time‐kill curves were conducted both with and without serum to determine the killing kinetic of pDADMAC‐PU. pDADMAC‐PU killed S. aureus, A. baumannii, and P. aeruginosa. The effect of pDADMAC‐PU on biofilm development was analyzed quantitatively and qualitatively. Quantitative analysis, colony‐forming unit assay, revealed that pDADMAC‐PU dressing produced more than eight log reduction in biofilm formation by each pathogen. Visualization of the biofilms by either confocal laser scanning microscopy or scanning electron microscopy confirmed these findings. In addition, it was found that the pDADMAC‐PU‐treated foam totally inhibited migration of bacteria through the foam for all three bacterial strains. These results suggest that pDADMAC‐PU is an effective wound dressing that inhibits the growth of wound pathogens both within the wound and in the wound dressing.